Some Copper(II) Complexes of Tetradentate ?-Ketoimines and their Adducts - Osowole, Aderoju A (Biological Sciences - PJSIR, 2006)
. The b-ketoimine ligands [CH3C(O)CHC(CH3)(-NH(CH2)nNH-)C(CH3)CHC(O)CH3]; n = 2, 6, 8, 9, their copper(II) chelates, and adducts with 2,2´-bipyridine (bipy) and 1,10-phenanthroline (phen) have been synthesized and characterized by elemental analysis, magnetic susceptibility, conductance, and infrared and electronic spectral measure- ments. The ligands were tetradentate in the complexes, using the imine N and keto O atoms in coordination. The room temperature magnetic moments of the complexes, suggest that they were magnetically dilute, while infrared and electronic spectra results were corroborative of a four coordinate square-planar geometry for the copper(II) chelates and a six coor- dinate octahedral geometry for their adducts. The compounds were non-electrolyte in nitromethane.